História da alfabetização de Ituiutaba: vivências no Grupo Escolar Governador Clóvis Salgado-1957-1971 - Cunha, Tânia Rezende Silvestre (2011)
This is a survey dedicated to reveal, from literacy practices experienced by two, one director and two students, the History of Literacy in the primary school Governor of Clovis Salgado in the city Ituiutaba, Minas Gerais, in the period 1957-1971. Accordingly, we sought to elucidate the stories of five people who lived the experience of teaching classes in literacy and being literate in a period that was used only to alphabetize the primers. We use booklets, pamphlets, laws and acts that supported the study to be unveiled that the literacy practices and methods, plans and evaluations in the primary school Governor of Clovis Salgado in the city Ituiutaba. From the qualitative analysis of interviews and all the historical and biographical survey of practices in the primary school in question, observed that the initial hypothesis that the suave would have been used in the study period was overruled. We realize, however, that the primers used for literacy at this time were the Primer for Children and The Most Beautiful Stories. We also note that in the same school during the same period and with the same working conditions, the literacy primers and used different methods. The Global Method and syllabic method were perceived and understood as teaching methods from the particular experience of literacy, contrary to the instructions in the basic primary education which directed its proposal for the specific use of the Global Method. Oral history, as the research methodology was fundamental for this study because it is from the voices of their own literacy that build the history of literacy in primary school Governador Clovis Salgado in the period 1957-1971. We sought to identify those who have literacy to understand which representations and appropriations made by them during that period and try to build a part of the history of literacy in Ituiutaba. After research, we understand that teachers, throughout their lives, were formed as literacy. The results show that the practices are value-laden representations and that these professionals have built and built throughout his life. Thus, their practices go beyond the rules laid down by school and bodies responsible for education in Minas Gerais.